Integration of Information and Optimization Models for Routing in City Logistics - Ehmke, Jan.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
As urban congestion continues to be an ever increasing problem, routing in these settings has become an important area of operations research. This monograph provides cutting-edge research, utilizing the recent advances in technology, to quantify the value of dynamic, time-dependent information for advanced vehicle routing in city logistics. The methodology of traffic data collection is enhanced by GPS based data collection, resulting in a comprehensive number of travel time records. Data Mining is also applied to derive dynamic information models as required by time-dependent optimization. Finally, well-known approaches of vehicle routing are adapted in order to handle dynamic information models. This book interweaves the usually distinct areas of traffic data collection, information retrieval and time-dependent optimization by an integrated methodological approach, which refers to synergies of Data Mining and Operations Research techniques by example of city logistics applications. These procedures will help improve the reliability of logistics services in congested urban areas.
Introduction -- City Logistics -- Attended Home Delivery -- Knowledge Discovery and Data Mining -- Analysis of Floating Car Data -- Provision of Distance Matrices -- Evaluation of Information Models -- Routing in City Logistics -- Evaluation of Optimization Models -- Conclusions and Outlook.
Keywords: Operations research; Decision making; Data mining; Regional economics; Spatial economics; Operations Research/Decision Theory; Data Mining and Knowledge Discovery; Regional/Spatial Science